Matching Efficiency and Business Cycle Fluctuations - Francesco Furlanetto; Nicolas Groshenny (Norges Bank, 2012)
A large decline in the efficiency of the U.S. labor market in matching unemployed workers and vacant jobs has been documented during the Great Recession. We use a simple New Keynesian model with search and matching frictions in the labor market to study the propagation of matching efficiency shocks. We show that the transmission of these disturbances and their importance for business cycle fluctuations depend crucially on the form of hiring costs and on the presence of nominal rigidities.
hdl:11250/2496832
Keywords: 330